PENGARUH PELATIHAN, INTEGRITAS DAN EFIKASI DIRI TERHADAP EFEKTIVITAS MANAJERIAL KEPALA SEKOLAH DI PROVINSI DKI JAKARTA - Haryanto Haryanto (Jurnal Good Governance, 2018)
Based on Principal competency Test Result on 2015, 92% under 65 from 0 – 100 scales. Between 5 aspects tested, managerial competence aspect got the lowest score. This research aims to analyze the impact of training, integrity, and self efficacy on the managerial effectiveness of the head of state primary school of Jakarta Provincial Education Office. The survey was conducted in this study with 172 samples of state primary school with random sampling technique. The data were processed with path analysis. The results showed that: (1) training effects positive directly on the managerial effectiveness. (2) Integrity effects positive directly on the managerial effectiveness. (3) Self efficacy effects positive directly on the managerial effectiveness. (4) Training effects positive directly on self-efficacy. (5) Integrity effects positive directly on self- efficacy. based on the findings it can be concluded that in order to improve the managerial effectiveness, it should be increased the teacher’s training, integrity, and self-efficacy. and to improve the self-efficacy, it should be increased the teasher’s training and integrity.Keywords: training, integrity, self-efficacy, the managerial effectiveness